Integrated technological system of biogas production - Чайковська, Євгенія Євстафіївна (Eastern-European Journal of Enterprise Technologies, 2013)
Existing support systems of biogas units operation do not always accurately take into account the temperature parameters of raw materials fermentation, which is caused by their high heat storage capacity. Moreover, under the fermentation temperature changes the wort consumption change functions as the regulating factor that can disrupt the required balance of fresh and fermented material. Analytical forecasting assessment of fermentation temperature change and the principle of intelligent control of heat pump energy supply have been proposed for changing the coolant consumption in the heat pump evaporator, depending on the temperature of discharged raw materials. This approach will provide the opportunity of predictive decision-making concerning the timely discharge of fermented materials in a biogas unit discharge mode and charging the equivalent consumption of fresh raw materials in the biogas unit charge mode. Using the discharged material in a heat pump in a discharge mode allows the decision-making on a temperature change of heating carrier in a charge mode. An integrated technological system of biogas production based on coordinated interaction of dynamic subsystems - biogas unit and the heat pump, allows, setting a balance between fresh and fermented raw materials, a constant biogas output under increased marketable value of a biogas unit up to 10-15%.